Overcoming the Odds: Toward a Molecular Profile of Long-Term Survival in Glioblastoma. Issue 10 (15th September 2020) - Richardson, Timothy E; Kumar, Ashwani; Xing, Chao; Hatanpaa, Kimmo J; Walker, Jamie M
Abstract: For over a century, gliomas were characterized solely by histologic features. With the publication of the WHO Classification of Tumours of the Central Nervous System, Revised 4th Edition in 2016, integrated histologic and molecular diagnosis became the norm, providing improved tumor grading and prognosis with IDH1/2 (isocitrate dehydrogenase 1 and 2) mutation being the most significant prognostic feature in all grades of adult diffuse glioma. Since then, much work has been done to identify additional molecular prognostic features, but the bulk of the progress has been made in defining aggressive features in lower grade astrocytoma. Although there have been several large case series of glioblastomas with long-term survival (LTS; overall survival ≥36 months), less is known about the clinical and molecular features of these cases. Herein, we review 19 studies examining LTS glioblastoma patients from 2009 to 2020 that include variable molecular analysis, including 465 cases with survival of 36 months or more (total n = 2328). These studies suggest that while there is no definitive molecular signature of long survival, younger age, IDH mutation, and MGMT (methyl guanine methyl transferase) promoter hypermethylation are associated with longer overall survival, and in IDH-wildtype tumors, chromosome 19/20 co-gain and lack of EGFR amplification, chromosome 7 gain/10 loss, and TERT promoter mutation are associated with LTS.